The Mitochondrial Citrate Carrier (SLC25A1) Sustains Redox Homeostasis and Mitochondrial Metabolism Supporting Radioresistance of Cancer Cells With Tolerance to Cycling Severe Hypoxia - Hlouschek, Julian; Hansel, Christine; Jendrossek, Verena; Matschke, Johann (Frontiers in Oncology, 2018)
Pronounced resistance of lung cancer cells to radiotherapy and chemotherapy is a major barrier to successful treatment. Herein, both tumor hypoxia and the up-regulation of the cellular antioxidant defence systems observed during malignant progression can contribute to radioresistance. We recently found that exposure to chronic cycling severe hypoxia/reoxygenation stress results in glutamine-dependent up-regulation of cellular glutathione (GSH) levels and associated radiation resistance opening novel routes for tumor cell-specific radiosensitization. Here we explored the role of the mitochondrial citrate carrier (SLC25A1) for the improved antioxidant defense of cancer cells with tolerance to acute and chronic severe hypoxia/reoxygenation stress and the use of pharmacologic SLC25A1 inhibition for tumor cell radiosensitization. Exposure to acute or chronic cycling severe hypoxia/reoxygenation stress triggered up-regulated expression of SLC25A1 in lung cancer, prostate cancer and glioblastoma cells in vitro. Interestingly, exposure to ionizing radiation (IR) further promoted SLC25A1 expression. Inhibition of SLC25A1 by 1,2,3-benzene-tricarboxylic acid (BTA) disturbed cellular and mitochondrial redox homeostasis, lowered mitochondrial metabolism, and reduced metabolic flexibility of cancer cells. Interestingly, exposure to ionizing radiation (IR) also promoted SLC25A1 expression. Even more important, combining IR with BTA was able to overcome radioresistance induced by adaptation to chronic cycling severe hypoxia/reoxygenation stress. This radiosensitizing effect of BTA-treated cells was linked to increased ROS and reduced DNA repair capacity. Of note, key findings could be reproduced when using the SLC25A1 inhibitor 4-Chloro-3-[[(3-nitrophenyl)amino]sulfonyl]-benzoic acid (CNASB). Even more important, in-silico analyses of publically available databases applying the Kaplan meier plotter tool (kmplot.com) revealed that over-expression of SLC25A1 was associated with reduced survival of lung cancer patients suggesting a potential link to aggressive cancers. We show that SLC25A1 can contribute to the increased antioxidant defense of cancer cells allowing them to escape the cytotoxic effects of IR. Since up-regulation of SLC25A1 is induced by adverse conditions in the tumor environment, exposure to IR, or both, pharmacologic inhibition of SLC25A1 might be an effective strategy for radiosensitization of cancer cells particularly in chronically hypoxic tumor fractions.